2012
DOI: 10.1080/09500839.2011.619507
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically driven grain boundary relaxation: a mechanism for cyclic hardening in nanocrystalline Ni

Abstract: Molecular dynamics simulations are used to show that cyclic mechanical loading can relax the non-equilibrium grain boundary (GB) structures of nanocrystalline metals by dissipating energy and reducing the average atomic energy of the system, leading to higher strengths. The GB processes that dominate deformation in these materials allow low-energy boundary configurations to be found through kinematically irreversible structural changes during cycling, which increases the subsequent resistance to plastic deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 33 publications
4
32
1
Order By: Relevance
“…It may therefore be expected that studies that did not minimize GB energy with respect to number of atoms may have inadvertently generated high-energy GBs [32,62]. However, in some cases, the lowest energy GB structures might not be the ones of interest, e.g., when investigating far from equilibrium states [35,87,88]. Sometimes, the atomic-level state of a GB might not even be relevant, e.g., for determining the distribution of intrinsic defects [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be expected that studies that did not minimize GB energy with respect to number of atoms may have inadvertently generated high-energy GBs [32,62]. However, in some cases, the lowest energy GB structures might not be the ones of interest, e.g., when investigating far from equilibrium states [35,87,88]. Sometimes, the atomic-level state of a GB might not even be relevant, e.g., for determining the distribution of intrinsic defects [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that local GB structure can be in a non-equilibrium state, one which contains excess boundary dislocations or free volume [14]. This non-equilibrium structure can be "relaxed" during annealing or deformation [25,42], and the boundary can reach a lower energy state.…”
Section: Methodsmentioning
confidence: 99%
“…81 This instability has been attributed to the mobility of high energy grain boundaries formed through electrodeposition, and it has been suggested that if properly conditioned through cyclic loading, the grain boundaries may relax without significant grain coarsening and loss of mechanical strength at ambient temperature. 81,82 However, the application of nominally pure LIGA nickel in load bearing configurations is expected to be quite limited on the basis that most conventional MEMS packaging processes use temperature excursions beyond the threshold for microstructural stability.…”
Section: A Liga Nimentioning
confidence: 99%